Kultur jaringan tanaman dan penerapannya untuk pengembangan genetik tanaman LPIU Unpatti - cida - [Tidak Terdaftar] ([Tidak Terdaftar], 1989)
Kultur jaringan tanaman dan penerapannya untuk pengembangan genetik tanaman ...